2019
DOI: 10.1103/physrevlett.122.207201
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetic Anisotropy Induced by Ligand LS Coupling in Layered Cr Compounds

Abstract: We propose a novel origin of magnetic anisotropy to explain the unusual magnetic behaviors of layered ferromagnetic Cr compounds (3d 3 ) wherein the anisotropy field varies from 0.01 T to ∼ 3 T on changing the ligand atom in a common hexagonal structure. The effect of the ligand p orbital spin-orbit (LS) coupling on the magnetic anisotropy is explored by using four site full multiplet cluster model calculations for energies involving the superexchange interaction at different spin axes. Our calculation shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 43 publications
7
52
1
Order By: Relevance
“…In principle, spin rotational invariance of a 3D magnetic system can be broken via dipolar interactions [10], singleion (magnetocrystalline) anisotropy [11], and/or anisotropic magnetic exchange interactions [12,13]. For layered honeycomb lattice ferromagnet such as CrI 3 [Figs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In principle, spin rotational invariance of a 3D magnetic system can be broken via dipolar interactions [10], singleion (magnetocrystalline) anisotropy [11], and/or anisotropic magnetic exchange interactions [12,13]. For layered honeycomb lattice ferromagnet such as CrI 3 [Figs.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the temperature dependence of the magnetic anisotropy of CrI 3 with those of CrBr 3 , it was concluded that the magnetic anisotropy in CrI 3 arises from a dominant uniaxial or single-ion anisotropy [24], which comes mostly from the , where the nearest-neighbor I atoms form an octahedral environment with 3 I above (dark purple) and 3 I below (light purple) the Cr layer. The Cr-I-Cr path forms an angle close to 90 degrees [12,13]. The Kitaev interactions between Cr 3+ atoms are marked as J xx , J yy , and J zz [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations